Contrasting Patterns of Genetic Isolation Among Diadromous, Landlocked, and Non‐Migratory Gobiid Fish Populations - Jeffery C. F. Chan; Bi Wei Low; Anthony Lau; Frank E. Rheindt; David Dudgeon; Jia Huan Liew (Molecular Ecology, 2026)
Dams can landlock populations of amphidromous fishes that formerly migrated between rivers and seas. However, the genetic consequences of these life‐cycle changes remain unclear. Rhinogobius is a speciose genus of freshwater gobies widely distributed in Asia, including non‐migratory R. duospilus and facultatively amphidromous R. similis . Using genome‐wide SNPs from Hong Kong, southern China, we compared the genetic diversity and structure of R. duospilus (six populations), non‐landlocked R. similis (three populations), and landlocked R. similis (four populations) that had been isolated for 58–106 years. We also used demographic modelling to simulate patterns of gene flow of a panmictic amphidromous population of R. similis fragmented by dam construction 60 years ago. Rhinogobius duospilus populations were deeply divergent, with low genetic diversity; interpopulation differentiation reflected the underlying paleodrainage architecture. In contrast, non‐landlocked R. similis populations were genetically homogenous with high genetic diversity. However, all four landlocked populations of R. similis were highly differentiated, with three populations above tall (> 15 m) dams exhibiting comparable genetic clustering to non‐migratory R. duospilus , although overall genetic diversity remained high. Demographic modelling of a landlocked R. similis population indicated negligible migration into the reservoir and none outward, in accordance with the high levels of genetic divergence among landlocked populations. The effective population size of the original amphidromous population was small (Ne = 81), but the population landlocked above the reservoir for 60 years grew eightfold (Ne = 679). Our modelling suggests that even a limited level of immigration was sufficient to minimize genetic drift and lessen interpopulation divergence.

Zooplankton as indicators of coastal water quality: a comparative study of PlanktonScope imaging and DNA metabarcoding of seawater and mesh-screened samples - Yingbei Peng; Chun Ming How; Dai Liu; Dumas Deconinck; Mei-Hong Zhao; Jack Chi-Ho Ip; Leo Lai Chan; Hongsheng Bi; Jian-Wen Qiu (Marine Environmental Research, 2026)

Paleocene to Eocene deformation and crustal shortening history of the Tanggula Range, Central Tibet - Wenjun Bi; Yalin Li; Zhongpeng Han; Chengshan Wang; Jiawei Zhang; Tiankun Xu; Dawei Lv; Chan Wang; Zining Ma; Haiyang He; Huan Chen (Global and Planetary Change, 2026)

Valorisation of spent cultivated meat media for recombinant FGF2 production in Lactococcus lactis - Juliana Rizal; Prashant Mainali; Jun Ping Quek; Lee Ling Tan; Jiawu Bi; Alson Jianchen Chan; Azra Anwar Gaffoor; Lamony Jian Ming Chew; Shigeki Sugii; Say Kong Ng; Dave Siak-Wei Ow; Fong Tian Wong (Systems Microbiology and Biomanufacturing, 2025)

Isotopic Analysis for Tracing Vertical Growth Trajectories of Hailstones - Xiangyu Lin; Haifan Zhang; Xiaofei Li; Qinghong Zhang; Andrew Heymsfield; Kai Bi; Chan-Pang Ng; Chong Wu; Dianli Gong (Advances in Atmospheric Sciences, 2025)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Identification and fine mapping of a QTL-rich region for yield- and quality-related traits on chromosome 4BS in common wheat (Triticum aestivum L.) - Jinghui Li; Huanhuan Zhao; Minghu Zhang; Chan Bi; Xiaoyuan Yang; Xintian Shi; Chaojie Xie; Baoyun Li; Guangbin Ma; Zhengang Ru; Tiezhu Hu; Mingshan You (Theoretical and Applied Genetics, 2024)

The male sterility of bread wheat line XN291S was resulted from the deletion of a large segment at the end of 6BS - Minghu Zhang; Jiazheng Yu; Qijun Xie; Shaozhe Wen; Jinghui Li; Chan Bi; Chaojie Xie; Zhongfu Ni; Rongqi Liang; Mingshan You (Euphytica, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

Dosage effect of anthocyanin biosynthesis in purple-grained wheat (Triticum aestivum L.) - Chan Bi; Chaoxiong Wei; Shuai Tian; Jinghui Li; Yufeng Zhang; Jun Ma; Mingshan You (Euphytica, 2023)

Synthesis of NaA zeolite via the mesoscale reorganization of submolten salt depolymerized kaolin: A mechanistic study - Xiaoling Chen; Ying Wang; Chan Wang; Jingdong Xu; Tiesen Li; Yuanyuan Yue; Xiaotao Bi; Lilong Jiang; Xiaojun Bao (Chemical Engineering Journal, 2023)

Clusterin Binding Modulates the Aggregation and Neurotoxicity of Amyloid-β(1–42) - Yun-Mi Kim; SuJi Park; Su Yeon Choi; Shin Bi Oh; MinKyo Jung; Chan-Gi Pack; Jung Jin Hwang; Eunyoung Tak; Joo-Yong Lee (Molecular Neurobiology, 2022)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Characterization of a major quantitative trait locus on the short arm of chromosome 4B for spike number per unit area in common wheat (Triticum aestivum L.) - Jinghui Li; Shaozhe Wen; Chaofeng Fan; Minghu Zhang; Shuai Tian; Wenjing Kang; Wenxin Zhao; Chan Bi; Qiuyan Wang; Shuang Lu; Weilong Guo; Zhongfu Ni; et al. (Theoretical and Applied Genetics, 2020)

Betulinic acid attenuates liver fibrosis by inducing autophagy via the mitogen-activated protein kinase/extracellular signal-regulated kinase pathway - Yuan Liu; Yanmeng Bi; Chan Mo; Ting Zeng; Sha Huang; Lei Gao; Xuegang Sun; Zhiping Lv (Journal of Natural Medicines, 2019)

Molecular characterization of a novel reovirus isolated from Pekin ducklings in China - Ying-Qi Zhu; Chuan-Feng Li; Zhuang-Li Bi; Zong-Yan Chen; Chun-Chun Meng; Gui-Jun Wang; Chan Ding; Guang-Qing Liu (Archives of Virology, 2015)

Development and Characterisation of Ursolic Acid Nanocrystals Without Stabiliser Having Improved Dissolution Rate and In Vitro Anticancer Activity - Ju Song; Yancai Wang; Yuelin Song; Hokman Chan; Chao Bi; Xiao Yang; Ru Yan; Yitao Wang; Ying Zheng (AAPS PharmSciTech, 2014)

Characteristics, loss and gain of atmospheric carbonyl compounds in winters of 2008–2010 in Pearl River Delta region, China - Yonglin Liu; Xinhui Bi; L. Y. Chan; Sheng Wen; Xinming Wang; Guoying Sheng; Jiamo Fu (Journal of Atmospheric Chemistry, 2013)